2021
DOI: 10.3928/01913913-20210108-02
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Game Playing in Amblyopia Therapy: A Randomized Clinical Trial

Abstract: Purpose: To compare the visual outcome of occlusion therapy with virtual reality game playing as a new therapy for children with amblyopia. Methods: This randomized clinical trial was performed on 50 children between 4 and 10 years old who had unilateral amblyopia. They were randomly divided into virtual reality and patching groups (n = 25 in each). The virtual reality group was trained binocularly using the virtual reality games through a head set for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“… 46 , 47 , 56 , 58 , 71 As reported by Waddingham et al, 84 Cleary et al, 86 Herbison et al, 87 Herbison et al, 88 Vedamurthy et al, 45 Hurd et al, 53 Halička et al, 55 Jhangian et al, 58 Tan et al, 60 and Xiao et al, 89 VA outcomes have shown comparable improvements through training using VR applications. Likewise, Rajavi et al, 49 Žiak et al, 16 Elhusseiny et al, 69 and Rajavi et al 50 have also made VA improvements, which reflected a promising application value for further research on this topic. Research regarding VR and observed changes in accommodative status and ocular structures have been reported by Turnbull & Phillips, 82 Elias et al, 13 Munsamy et al, 66 Yoon et al, 67 and Panfili et al 65 According to Turnbull & Phillips, 82 after a brief duration of VR usage, there was a considerable change in choroidal thickness.…”
Section: Resultsmentioning
confidence: 97%
“… 46 , 47 , 56 , 58 , 71 As reported by Waddingham et al, 84 Cleary et al, 86 Herbison et al, 87 Herbison et al, 88 Vedamurthy et al, 45 Hurd et al, 53 Halička et al, 55 Jhangian et al, 58 Tan et al, 60 and Xiao et al, 89 VA outcomes have shown comparable improvements through training using VR applications. Likewise, Rajavi et al, 49 Žiak et al, 16 Elhusseiny et al, 69 and Rajavi et al 50 have also made VA improvements, which reflected a promising application value for further research on this topic. Research regarding VR and observed changes in accommodative status and ocular structures have been reported by Turnbull & Phillips, 82 Elias et al, 13 Munsamy et al, 66 Yoon et al, 67 and Panfili et al 65 According to Turnbull & Phillips, 82 after a brief duration of VR usage, there was a considerable change in choroidal thickness.…”
Section: Resultsmentioning
confidence: 97%
“…This is the first study to measure and compare the efficacy and efficiency of supervised outpatient dichoptic action video gaming using VR goggles to objectively monitored occlusion therapy in 4–12‐year‐old children with newly diagnosed amblyopia. While several published studies (Barollo et al, 2017; Gambacorta et al, 2018; Gao et al, 2018; Herbison et al, 2016; Holmes et al, 2016; Huang et al, 2022; Li et al, 2015b; Manh et al, 2018; Mezad‐Koursh et al, 2018; Portela‐Camino et al, 2018; Rajavi et al, 2021) included subjects with a history of occlusion for amblyopia, it is unclear whether previous treatment could be a hindrance or an aid to acuity improvements subsequently gained through dichoptic therapy. Although we started with 96 recruited children, only 33 could be randomized: after 16 weeks of glasses adaptation, a third of the originally recruited children no longer had an interocular VA difference ≥0.20 logMAR and no longer qualified as amblyopic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing gaming with occlusion therapy in children have not monitored compliance electronically (Holmes et al, 2016; Jost et al, 2022; Kelly et al, 2016; Manh et al, 2018; Rajavi et al, 2021). Some studies have investigated only the effectiveness of gaming or dichoptic movie watching and did not compare with occlusion therapy (Barollo et al, 2017; Birch et al, 2015; Bossi et al, 2017; Gambacorta et al, 2018; Gao et al, 2018; Herbison et al, 2016; Huang et al, 2022; Kelly et al, 2018; Li et al, 2015a; Mansouri et al, 2014; Mezad‐Koursh et al, 2018; Portela‐Camino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this evidence, VR dichoptic and PL treatment appears to be a powerful tool for visual function restoration in these diseases. However, little evidence is available on whether dichoptic VR treatment could improve visual acuity in patients with amblyopia [23].…”
mentioning
confidence: 99%